PENGUATAN PARTISIPASI MASYARAKAT DALAM PERENCANAAN PEMBANGUNAN PERTANIAN (STUDI KASUS KABUPATEN PADANG PARIAMAN) - Rahmedi Yonis (Jurnal Pembangunan Nagari, 2016)
This study aimed to reveal the strengthening of participatory in optimizing the participation of stakeholders in the planning of agricultural development in the region. The research methode used descriptive quantitative analysis. The result showns that participation breadth, participation depth, participation channels, and integrated participation influenced stakeholder to contribute in agriculture development planning. Therefore, this research gives recomendation, where participatory model is build by strenghten four characteristic participation.